Respostas

2013-12-07T18:47:04-02:00
A - F(G(2))=
F(G(2) =4 . 2 + 3)
F(G(2) = 11)
F(11) = 121 + 33 + 2 
F(11) = 156

B - G(F(1)) =
G(F(1) = 1 + 3 + 2)
G(F(1) = 6)
G(6) = 24 + 3 
G(6) = 27

C - G(G(2)) =
G(G(2) = 8 + 3 )
G(G(2) = 11)
G(11) = 44 + 3
G(11) = 47

D - F(F(1)) =
F(F(1) = 1 + 3 + 2)
F(F(1) = 6)
F(6) = 36 + 18 + 2
F(6) = 56
1 5 1
2013-12-07T18:53:55-02:00
F(g(2))=4.2 +3 =11 -> f(11)= 121+33+2= 154

G(f(1))= 1+3+2= 6 -> g(6)=24+3=27

G(g(2))= 8+3=11-> g(11)= 44+3= 47

F(f(1))= 1+3+2=6 -> f(f(6))=36+18+2= 56
1 5 1